Effect of heating on onion (Allium cepa L.) antiplatelet activity and pungency sensory perception - Cavagnaro, Pablo; Sance, Maria Mirta; Galmarini, Claudio Romulo (Sage Publications, 2019)
Onion, in its raw form, is recognized as an antiplatelet agent that may contribute to the prevention of cardiovascular disease. In raw onions, the content of pyruvate, is significantly correlated with antiplatelet activity (AA) and the sensory perception of pungency. However, onion is generally cooked before consumption. Herein, we examine the effect of heating — using different boiling intensities — on the in vitro antiaggregatory activity (IVAA), the pyruvate concentration and the flavor (pungency) of crushed-onion samples. In general, heating is detrimental for onion AA. Boiling for 3 min has no significant effect on platelet aggregation, as compared to raw onion. Heating for 46 min completely suppresses IVAA, whereas samples boiled for > 20 min have pro-aggregatory effects. Significant differences in AA are found between the blood donors. Pyruvate content is not reduced after 30 min boiling. Pungency ratings decrease with the intensity of the heat treatment. Strong significant positive correlations are found between IVAA and pungency, but not between pyruvate and the former two variables. Our results suggest that: (i) in order to obtain the maximum health benefits onions should be eaten raw or moderately cooked, (ii) extensive heating may result in pro-aggregatory effects, (iii) pyruvate is not a good indicator of AA in cooked onions, (iv) the decrease in IVAA and pungency during onion cooking may be due to degradation of sulfur compounds (e.g. thiosulfinates) which are, likely, less tolerant than pyruvate to the high temperatures.